Freedom, nature, and world - Loptson, Peter (Collection Philosophica., 2007)
Freedom, Nature, and World is a collection of essays by Peter Loptson which examine issues posed by a broadly naturalistic view of the world, which Loptson defends while also exploring some of the challenges it confronts. Papers on freedom, Kant, Christianity, Homer, the history of analytic philosophy, the place of humanity in nature, and other topics, are brought together within a synoptically naturalistic purview. All the essays rest on, and in some cases extend, that synoptic perspective, which seeks to encompass both a scientific understanding of humankind in the natural world and the comp.